2020
DOI: 10.1021/acsami.0c07840
|View full text |Cite
|
Sign up to set email alerts
|

High Fluorescence Rate of Thermally Activated Delayed Fluorescence Emitters for Efficient and Stable Blue OLEDs

Abstract: A lack of an efficient and stable blue device is a critical factor restricting the development of organic light-emitting diode (OLED) technology that is currently expected to be overcome by employing thermally activated delayed fluorescence (TADF). Here, we investigate the TADF and electroluminescence (EL) performance of six carbazole/triphenyltriazine derivatives in different hosts. A good linearity between lg(LT50/k F 2 ) and the EL emission wavelength is found, where LT50 is the half-life of the devices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 53 publications
(145 reference statements)
1
39
2
Order By: Relevance
“…Recently, using an indolocarbazole/triphenyltriazine derivative (ICz-TRZ) as a luminescent material, we fabricated a stable blue TADF device successfully, which has the color coordinate CIE of 0.14, 0.19 and an LT 50 of up to 95 h with an L 0 of 1000 cd/m 2 . 23 Note that bluish-green TADF devices could be much more stable than the blue TADF OLEDs as mentioned above. 44,45 Some preliminary studies based on controlled experiments indicated that blue TADF OLEDs could be much more stable than blue PHOLEDs.…”
Section: Overview On the Lifetime Studies Of Blue Oledsmentioning
confidence: 87%
See 3 more Smart Citations
“…Recently, using an indolocarbazole/triphenyltriazine derivative (ICz-TRZ) as a luminescent material, we fabricated a stable blue TADF device successfully, which has the color coordinate CIE of 0.14, 0.19 and an LT 50 of up to 95 h with an L 0 of 1000 cd/m 2 . 23 Note that bluish-green TADF devices could be much more stable than the blue TADF OLEDs as mentioned above. 44,45 Some preliminary studies based on controlled experiments indicated that blue TADF OLEDs could be much more stable than blue PHOLEDs.…”
Section: Overview On the Lifetime Studies Of Blue Oledsmentioning
confidence: 87%
“…A small amount of the narrow bandgap coupling products could quench the emission from new molecules effectively. 62,85 As found in some TADF systems mentioned above, 15,[20][21][22][23] efficient and stable blue TADF OLEDs could be achieved by employing a TADF emitter with relatively large ΔE ST and long TADF lifetime. A possible explanation is that the S 1 state of most TADF molecules is a large-polarity CT state, that is, a diradical state.…”
Section: Degradation Mechanisms In Blue Tadf Oledsmentioning
confidence: 91%
See 2 more Smart Citations
“…[ 7,8 ] Furthermore, the fluorescent radiative decay rate constant ( k r ) of TADF emitters is also an important factor for the device stability as well. [ 11,12 ] In addition to the rational molecular design of TADF emitters for having a longer device operational lifetime, the choice of host materials should have a pronounced effect on device stability. In fact, it has been reported that the device operational stability of TADF or phosphorescent (Ph) OLEDs are significantly increasing when chemically stable materials are utilized as the host.…”
Section: Introductionmentioning
confidence: 99%